Burnishing of ultra high molecular weight poly ethylene. (2021) - Ashish, Valluri; Prasanna Kumar Reddy, Sabbella; Kannan, C.; Oyyaravelu, R.; Balan, A.S.S.
Abstract: Ultra-high molecular weight polyethylene (UHMWPE) has been a choice for knee and hip implants since a very long time due to its outstanding tribological properties. UHMWPE has many applications other than biomedical implants like hydrodynamic bearings and marine applications. The main objective of this research work is to enhance the surface properties of UHMWPE and eventually increase its life expectancy for the implants. For this purpose, the UHMWPE sheet has been milled to give it a required shape and then ball burnished with a carbide ball of 6 mm diameter under two different environments viz. room and cryogenic with three different burnishing strategic patterns. A constant load of 150 N is maintained by the tool on UHMWPE sample with a burnishing feed of 4000 mm/min along with a step over a distance of 0.06 mm after every pass for three different carefully chosen burnishing patterns. To understand the wear behaviour of the material, wear test has been performed on reciprocating wear testing machine with a stainless-steel ball as a pin for 6500 cycles in the medium of Hank's balanced salt solution (HBSS) as a lubricating agent and to maintain the pH value which is same as in the human body. The lowest average surface roughness (Ra = 0.52 µm) is reported for the second strategy pattern which gets burnished under the cryogenic environment. This sample also exhibited better wear resistance than other samples burnished under different environments and using different strategic patterns.